Seasonal variability of the subpolar gyres in the Southern Ocean: a numerical investigation based on transfer operators - M. Dellnitz; G. Froyland; C. Horenkamp; K. Padberg-Gehle; A. Sen Gupta (Nonlinear Processes in Geophysics, 2009)
The detection of regions in the ocean that are coherent over an extended period of time is a fundamental problem in many oceanic applications. For instance such regions are important for studying the transport of marine species and for the distribution of nutrients. In this study we demonstrate the efficacy of transfer operators in detecting and analysing such structures. We focus first on the detection of the Weddell and Ross Gyre for the four seasons spanning December 2003–November 2004 within the 3-D oceanic domain south of 30° S, and show distinct seasonal differences in both the three-dimensional structure and the persistence of the gyres. Further, we demonstrate a new technique based on the discretised transfer operators to calculate the mean residence time of water within parts of the gyres and determine pathways of water leaving and entering the gyres.